Very early environmental enrichment protects against apoptosis and improves functional recovery from hypoxic–ischemic brain injury - Lee, Hoo Young; Song, Suk-Young; Hwang, Jihye; Baek, Ahreum; Baek, Dawoon; Kim, Sung Hoon; Park, Jung Hyun; Choi, Sungchul; Pyo, Soonil; Cho, Sung-Rae (Frontiers in Molecular Neuroscience, 2023)
Appropriate rehabilitation of stroke patients at a very early phase results in favorable outcomes. However, the optimal strategy for very early rehabilitation is at present unclear due to the limited knowledge on the effects of very early initiation of rehabilitation based on voluntary exercise (VE). Environmental enrichment (EE) is a therapeutic paradigm for laboratory animals that involves complex combinations of physical, cognitive, and social stimuli, as well as VE. Few studies delineated the effect of EE on apoptosis in very early stroke in an experimental model. Although a minimal benefit of early rehabilitation in stroke models has been claimed in previous studies, these were based on a forced exercise paradigm. The aim of this study is to determine whether very early exposure to EE can effectively regulate Fas/FasL-mediated apoptosis following hypoxic–ischemic (HI) brain injury and improve neurobehavioral function. C57Bl/6 mice were housed for 2 weeks in either cages with EE or standard cages (SC) 3 h or 72 h after HI brain injury. Very early exposure to EE was associated with greater improvement in motor function and cognitive ability, reduced volume of the infarcted area, decreased mitochondria-mediated apoptosis, and decreased oxidative stress. Very early exposure to EE significantly downregulated Fas/FasL-mediated apoptosis, decreased expression of Fas, Fas-associated death domain, cleaved caspase-8/caspase-8, cleaved caspase-3/caspase-3, as well as Bax and Bcl-2, in the cerebral cortex and the hippocampus. Delayed exposure to EE, on the other hand, failed to inhibit the extrinsic pathway of apoptosis. This study demonstrates that very early exposure to EE is a potentially useful therapeutic translation for stroke rehabilitation through effective inhibition of the extrinsic and intrinsic apoptotic pathways.